2006
DOI: 10.1016/j.cell.2006.07.031
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern-Based Method for the Identification of MicroRNA Binding Sites and Their Corresponding Heteroduplexes

Abstract: We present rna22, a method for identifying microRNA binding sites and their corresponding heteroduplexes. Rna22 does not rely upon cross-species conservation, is resilient to noise, and, unlike previous methods, it first finds putative microRNA binding sites in the sequence of interest, then identifies the targeting microRNA. Computationally, we show that rna22 identifies most of the currently known heteroduplexes. Experimentally, with luciferase assays, we demonstrate average repressions of 30% or more for 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
1,499
0
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,854 publications
(1,519 citation statements)
references
References 50 publications
8
1,499
0
12
Order By: Relevance
“…Our results address this question using a combination of experimental approaches that allowed us to monitor the cardiac levels of these splice variants in different in vivo settings. Using the rna22 algorithm (Miranda et al, 2006), we identified putative binding sites for several cardiac miRNAs (Thum et al, 2007) in the human ankrd1 intron 8 sequence suggesting that the expression of intron-8-retained and intronless ankrd1 transcripts might be differentially regulated in the heart. However, in both pig and human neonatal heart the expression of intronless and ankrd1-i8 variants was found to be similarly co-regulated in a chamber-dependent manner (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results address this question using a combination of experimental approaches that allowed us to monitor the cardiac levels of these splice variants in different in vivo settings. Using the rna22 algorithm (Miranda et al, 2006), we identified putative binding sites for several cardiac miRNAs (Thum et al, 2007) in the human ankrd1 intron 8 sequence suggesting that the expression of intron-8-retained and intronless ankrd1 transcripts might be differentially regulated in the heart. However, in both pig and human neonatal heart the expression of intronless and ankrd1-i8 variants was found to be similarly co-regulated in a chamber-dependent manner (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Databases for predicted target genes consisted of miRanda,26 RNA22,27 and Targetscan,28 as well as miRWalk 2.0 25. Putative target genes were identified when the miRNA‐target interactions were verified by three or more databases.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding 21-23 nucleotide RNA molecules, which regulate the production of proteins from mRNA [5,6]. They are found in the cell free fraction of blood, including serum, and can be reliably measured from frozen stored samples [7].…”
Section: Introductionmentioning
confidence: 99%